Operationalizing urban resilience through a framework for adaptive co-management and design: five experiments in urban planning practice and policy - Collier, Marcus (My University, 2016)
The emergent discourse on social-ecological resilience can be understood as a response to the rapid pace of change and severe challenges facing urban areas. This paper reports on one strand of research being carried out as part of the EU FP7 TURAS project (Transitioning to Urban Resilience and Sustainability) that aims to gain insight into the implications of social-ecological resilience thinking on urban planning practice and policy by presenting a unique, trans-disciplinary perspective that has been developed collaboratively between academic, local government and SME partners. A framework for adaptive co-management and design is introduced as a basis for the operationalisation of urban resilience, highlighting the need to actively solve problems collaboratively by exercising imagination and creativity, and presenting a new and potentially fertile source for innovation. Five experiments exploring urban planning practices relating to the framework are put forward as examples of urban resilience in practice: an online crowd-sourcing application for mapping underused spaces; an interactive timeline tool for identifying drivers of change over time; a guidance and signposting tool to help community projects overcome resource barriers; an epistemic network of citizens that exchanges knowledge and resources relating to underused spaces; and an online portal that provides visibility for community groups or projects, and facilitates horizontal networking. The paper describes each experiment, sets out the aims and theoretical contexts, records any initial findings, and reflects on the potential and limitations. Initial findings are discussed relating to the challenges of crowd-sourcing spatial or historical data, and the resource commitment required for the emerging practices. It is observed that the experiments attempt to address fundamental issues in urban planning practice and policy, and involve established and familiar activities. The paper concludes that the research provides insight into what urban resilience might mean in practice and that each experiment has the potential to make a tangible contribution to the transition to urban resilience and sustainability.
PUBLISHED
Abstract: The emergent discourse on social-ecological resilience can be understood as a response to the rapid pace of change and severe challenges facing urban areas. This paper reports on one strand of research being carried out as part of the EU FP7 TURAS project (Transitioning to Urban Resilience and Sustainability) that aims to gain insight into the implications of social-ecological resilience thinking on urban planning practice and policy by presenting a unique, trans-disciplinary perspective that has been developed collaboratively between academic, local government and SME partners. A framework for adaptive co-management and design is introduced as a basis for the operationalisation of urban resilience, highlighting the need to actively solve problems collaboratively by exercising imagination and creativity, and presenting a new and potentially fertile source for innovation. Five experiments exploring urban planning practices relating to the framework are put forward as examples of urban resilience in practice: an online crowd-sourcing application for mapping underused spaces; an interactive timeline tool for identifying drivers of change over time; a guidance and signposting tool to help community projects overcome resource barriers; an epistemic network of citizens that exchanges knowledge and resources relating to underused spaces; and an online portal that provides visibility for community groups or projects, and facilitates horizontal networking. The paper describes each experiment, sets out the aims and theoretical contexts, records any initial findings, and reflects on the potential and limitations. Initial findings are discussed relating to the challenges of crowd-sourcing spatial or historical data, and the resource commitment required for the emerging practices. It is observed that the experiments attempt to address fundamental issues in urban planning practice and policy, and involve established and familiar activities. The paper concludes that the research provides insight into what urban resilience might mean in practice and that each experiment has the potential to make a tangible contribution to the transition to urban resilience and sustainability.
Keywords: Resilience thinking; Adaptive co-management; Co-design; Community resilience; Underused spaces; Smart & Sustainable Planet; adaptive co-management; resilience; urban resilience